Phytochemistry Of Calophyllum Havilandii P.F. Stevens And Calophyllum Lowei Planch. & Triana And Their Biological Activities - Zailan, Ahmad Alif Danial (2024)
Plants from the genus Calophyllum (Calophyllaceae) is a treasure trove of various interesting phytochemicals with impressive structural diversity. These phytochemical constituents were often discovered as derivatives in the classes of phenolics, such as xanthones, coumarins, chromanones, phloroglucinols, and flavonoids. Many of them are proven to exhibit wide range of pharmacological as well as biological activities, such as cytotoxic, anti-viral, anti-inflammatory, and anti-microbial. In this study, the process of extraction, isolation, and characterization of phytochemicals were conducted on the stem bark of two endemic Malaysian Calophyllum species from Sarawak, namely Calophyllum havilandii and Calophyllum lowei. All of the isolated phytochemicals were characterized and elucidated using extensive spectroscopic techniques such as MS, IR, UV, and NMR.